The effect of Guidance and Counselling on Students’ Discipline in Secondary Schools of Ruhinda North, Mitooma District, Uganda - Korugyendo, Placidia; Kintu, Denis; Ahabwe, Emmanuel (East African Journal of Education Studies, 2022)
Stakeholders are concerned about students’ indiscipline in secondary schools of Ruhinda North, Mitooma District, Uganda. The study assessed the effectiveness of guidance and counselling in promotion of discipline of learners in secondary schools of Ruhinda North, Mitooma District, Uganda. The study used descriptive research where both quantitative (questionnaires), and qualitative (interviews) approaches were used during. A total of 234 who were drawn from 600. The study findings revealed that major causes of students’ indiscipline in secondary schools of Ruhinda North , Mitooma District include; incompetent leadership, poor teaching by some teachers, poor feeding practices, and too much freedom in schools. The study findings showed that counsellors collect and keep up to dated students’ records, Counsellors disseminate vital information concerning academics to students, schools have well-furnished offices and rooms to carry out guidance and counselling activities and there is the proper motivation of students from the school administration during guidance and counselling sessions. The results indicated that guidance and counselling is statistically significant related to discipline of students in secondary schools of Ruhinda North, Mitooma District (r=0.159, P = 0.024 < 0.05). It was concluded the major causes of students’ indiscipline in secondary schools in Ruhinda North, Mitooma District were; poor leadership, poor teaching methods, absenteeism of teachers, and poor feeding practices. It was also concluded that there was effective guidance and counselling. Guidance and counselling have a positive influence on students’ discipline. Therefore, effective guidance and counselling promote students’ discipline. It was recommended that Ministry of Education should put more efforts towards ensuring acceptable moral training among students.